2015
DOI: 10.1007/s10266-015-0214-5
|View full text |Cite
|
Sign up to set email alerts
|

Performance of NiTi endodontic instrument under different temperatures

Abstract: The purpose of this study was to test nickel titanium (NiTi) instrument performance under different surrounding temperatures. Twenty-four superelastic NiTi instruments with a conical shape comprising a 0.30-mm-diameter tip and 0.06 taper were equally divided into 3 groups according to the temperature employed. Using a specially designed cyclic fatigue testing apparatus, each instrument was deflected to give a curvature 10 mm in radius and a 30° angle. This position was kept as the instrument was immersed in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
43
1
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 35 publications
4
43
1
1
Order By: Relevance
“…This is in agreement with previous studies (6,7) in which increasing the temperature was found to decrease the NCF. In one study, NiTi rotary Basic Research-Technology instruments were made from wire to a tip size of 30 with a .06 taper (6). Eight files were rotated at each tested temperature (10 C, 37 C, and 50 C) until fracture; a lower NCF was observed at 50 C and 37 C compared with 10 C (6).…”
Section: Discussionsupporting
confidence: 94%
“…This is in agreement with previous studies (6,7) in which increasing the temperature was found to decrease the NCF. In one study, NiTi rotary Basic Research-Technology instruments were made from wire to a tip size of 30 with a .06 taper (6). Eight files were rotated at each tested temperature (10 C, 37 C, and 50 C) until fracture; a lower NCF was observed at 50 C and 37 C compared with 10 C (6).…”
Section: Discussionsupporting
confidence: 94%
“…A recent clinical study showed room temperature sodium hypochlorite placed in root canals rapidly approaches body temperature (); therefore, instruments are expected to work at body temperature during clinical use. Moreover, recent studies have clearly demonstrated that there is a decrease in CF with increased temperature, moreover in martensitic instruments (). Two different studies have tested ProTaper Universal F2 at room and body temperature and found a similar reduction in CF ().…”
Section: Discussionmentioning
confidence: 99%
“…24 However, several factors can affect the resistance of NiTi endodontic instruments, such as the manufacturing process, metallurgical design, instrument size, taper, helix angle, cross-sectional design, core diameter, file kinematics, heat treatment applied to the file, 25,26,27 or even the temperature to which the instrument is subjected. 20,28,29 Many cyclic fatigue test devices may be used with static or dynamic test models. In this study, the model used for the cyclic fatigue test was static, in which an instrument-fixed working length is bended and then rotated until fracture occurs with no axial movement, allowing for a precise trajectory in the simulated artificial canal in a stainless steel block, as used in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…19,21,32,33 However, recent findings have shown that NiTi martensite instruments operating at body temperature (37 o C) show a significant decrease in flexural resistance and consequently in NCF, since heating may induce a transition to a stiffer austenite phase, which is more susceptible to fatigue failure. 20,28,29,34 The present study compared the cyclic fatigue resistance of the reciprocating Genius File and EdgeFile with WaveOne Gold. According to our results, the cyclic fatigue resistance of both Genius and EdgeFile systems was higher than that of WaveOne Gold, evidencing the highest fatigue resistance for EdgeFile.…”
Section: Discussionmentioning
confidence: 99%